Pelatihan homestay dan inovasi kuliner sebagai strategi pemberdayaan perempuan dalam pariwisata - Rini Kartika Hudiono; Evi Maria; Suharyadi Suharyadi (Unri Conference Series: Community Engagement, 2020)
The community service activities conducted in Srumbung Gunung was to involve women. Dusun Srumbung Gunung is developing a creative peace tourism village and the tourist products developed is a package program of live. In order to involve women in tourism, the training of homestay and culinary innovation was held, in which some women lost their job due to Covid 19 Pandemic. The method used was explorative qualitative with some stages. The first stage was to identify the house availability for homestay through interview and observation. Next was to identify the ingredient available and produced locally. The third stage was to research the type of snack which can be made with the available ingredient, good flavour and good price, easy to make with simple tools. Besides, the product can be produced as typical and unique food for tourists. Following this step was to choose women involved especially those who are interested in the food business and owning basic baking skill. The fifth step was the training of homestay with the concept of Clean, Healthy, Safe and Environmentally Sustainable, the training of culinary innovation was making bolen pisang and tape. The last stage was the mentoring process of homestay and the start-up food business of bolen pisang and tape. Two of the twenty-two women joined has started to prepare the business. The results showed that women involvement in tourism limited to fund, entrepreneurship experience and skill and the responsibility as housewives.